To study and compare the obstetric and neonatal outcome of pregnancies complicated with hypothyroidism amongst antenatally detected and treated hypothyroid patients and patients found to be hypothyroid at the time of labor - Shah, Parmanand K.; Chaudhari, Hemangi K.; Mathias, Delina A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To evaluate pregnancy outcome in women with elevated serum thyroid stimulating hormone (TSH) values as compared to those in whom hypothyroidism was treated. Methods: A prospective interventional comparative study was conducted in the department of obstetrics and gynaecology in King Edward Memorial Hospital, Mumbai, India from 2014 to 2015. A cohort of 60 hypothyroid patients was divided into two groups of 30 each. Group 1, euthyroid (treated hypothyroid) and group 2, hypothyroid at the time of labor and pregnancy outcomes were compared. Results: All patients in group 1 delivered at term; whereas in group 2, 9 (30%) patients had preterm deliveries and 21 (70%) delivered at term, amongst which 5 patients delivered babies with severe intrauterine growth restriction (IUGR). Neonatal intensive-care unit (NICU) admission were required for 3 neonates in group 1 and 11 (36.67%) neonates in group 2. Group 1 delivered 5 (16.67%) low birth weight babies (weight <2.5 kg) whereas 16 (53.34%) babies had low birth weight in group 2. Conclusions: Treatment of patients diagnosed with hypothyroidism during pregnancy significantly (p value <0.05) reduced the risk of preterm labor, low birth weight, need for NICU admission.